Regulation of neurons in the dorsal motor nucleus of the vagus by SIRT1 - Jiang, Yanyan; Zsombok, Andrea (Frontiers in Neuroscience, 2014)
Neurons in the dorsal motor nucleus of the vagus (DMV) play a critical role in the regulation of autonomic functions. Previous studies indicated that central activation of sirtuin 1 (SIRT1) has beneficial effects on homeostasis, most likely via modulation of the autonomic output. Sirtuins are NAD+-dependent deacetylases and have been associated with longevity. SIRT1 is one of the best-characterized sirtuins expressed in mammals, and may be involved in the regulation of metabolism. Resveratrol, a SIRT1 activator reduced hyperglycemia likely through activation of vagal output; however, the cellular mechanisms of action have not been determined. In this study, whole-cell patch-clamp electrophysiology on acute brainstem slices was used to test the hypothesis that activation of SIRT1 with resveratrol enhances neurotransmission in DMV neurons. Application of resveratrol increased the frequency of spontaneous excitatory postsynaptic currents (sEPSC). This effect was KATP channel-dependent and was prevented with pre-application of SIRT1 inhibitor, EX527. Resveratrol also increased miniature EPSC (mEPSC) frequency without change in amplitude. Furthermore, our data demonstrated that resveratrol regulates excitatory neurotransmission in a PI3 kinase-dependent manner, since wortmannin, a PI3K inhibitor prevented the increase of mEPSC frequency caused by resveratrol. In conclusion, our data demonstrate that resveratrol via SIRT1 increases excitatory neurotransmission to DMV neurons. These observations suggest that activation of SIRT1 may regulate the function of subdiaphragmatic organs through controlling the activity of parasympathetic DMV neurons.